Evaluation of User Satisfaction in Web-based Library Information Systems: A Systematic Literature Review - Faradina Faradina; Taqwa Hariguna; Fandy Setyo Utomo (SISTEMASI, 2026)
The transformation of library management today is highly influenced by the acceleration of information and communication technology (ICT), particularly through the adoption of web-based information systems. While these systems can optimize productivity and service accessibility, their effectiveness ultimately depends on the level of user satisfaction. This study evaluates various user satisfaction assessment methodologies through a Systematic Literature Review (SLR) using the PRISMA protocol on 25 selected articles published between 2020 and 2024. The findings indicate a shift in the dominance of evaluation tools toward the Human-Organization-Technology Fit (HOT-Fit) model and the Net Promoter Score (NPS). Key determinants of satisfaction were identified in terms of information quality, system reliability, and responsiveness of technical support.